Class and creativity in fashion education: A comparison of the pedagogies of making and design at British technical schools and art and design schools, 1870s‐1950s. (1st October 2021) - Bide, Bethan
Discourses of creativity play a crucial role in shaping cultural perceptions of what constitutes creative labour, who performs it and where it is located. This article explores the historical role that businesses, policy-makers and education providers played as co-producers of discourses about creativity in British fashion and textile design education. Beginning with the emergence of new vocational courses for textile design and manufacture in the 1870s, it traces how the language used to describe conceptions of creativity evolved in relation to educational provision for textiles, dressmaking and, later, fashion over the first half of the twentieth century. During this period, creativity became associated with labour related to designing fashion and textile goods ‐ such as illustration ‐ rather than the labour of making them. This shift resulted from the establishment of fashion and textile design as respected courses within art and design schools, which backed the ideal of a professional designer. It was implemented at the expense of, and with the effect of undermining the creative labour of staff and students in vocational trade schools. As a result, this article challenges the idea that the development of fashion and textile design courses in art and design schools democratized the creative labour of design in the British fashion industry by opening opportunities for the middle-classes. Rather, it finds that discourses around creative labour worked to exclude the creativity of the predominantly working-class students at technical schools, with long-term implications for the relationship between socio-economic status and access to the creative industries.